2013
DOI: 10.3171/2013.1.jns121153
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of high-frequency hearing loss after microvascular decompression for hemifacial spasm

Abstract: High-frequency hearing loss occurs in a significant number of patients following MVD surgery for HFS. Drill-induced noise and transient loss of CSF during surgery may impair hearing in the high-frequency ranges on both the ipsilateral and contralateral sides, with the ipsilateral side being more affected. Changes in intraoperative BAEPs during MVD for HFS were not useful in predicting HFHL. Follow-up studies and repeat audiological examinations may be helpful in evaluating the time course and prognosis of HFHL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…28 Analysis was performed at various stages during the surgery: 1) baseline, after intubation and positioning of the patient; 2) dura open, the epoch when the opening of the dura mater was documented; 3) change max, the maximum change in latency or amplitude recorded compared with average baseline waveform, including epochs when the responses were completely lost; and 4) on skin, the last epoch recorded.…”
Section: Analysis Of Neurophysiological Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Analysis was performed at various stages during the surgery: 1) baseline, after intubation and positioning of the patient; 2) dura open, the epoch when the opening of the dura mater was documented; 3) change max, the maximum change in latency or amplitude recorded compared with average baseline waveform, including epochs when the responses were completely lost; and 4) on skin, the last epoch recorded.…”
Section: Analysis Of Neurophysiological Parametersmentioning
confidence: 99%
“…Pure-tone audiometry was performed as described by Ying et al 28 Preoperative audiometry was performed between 1 and 142 days (mean 9.2 days, median 1 day). Postoperative audiometry was performed between 1 and 16 days (mean 2.1 days, median 1 day).…”
Section: Audiometrymentioning
confidence: 99%
“…HFHL probably was not secondary to stretching of the auditory nerve during MVD but likely was induced by high-intensity drilling noise during craniotomy early in the procedure. 34 Studies performed on hair cells in animal models have reported evidence of reestablished signal transduction upon regeneration of the tip links of hair cells in cultured explants 6 hours after the stimulus, 35 or in vivo after 24-120 hours. 15 The time course of hair cell tip link regeneration suggests that this process may underlie recovery from temporary threshold shift induced by noise exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The design of the study and the analysis of the data are intended to be similar to those used in a study published previously by many of the present paper's authors. 34 …”
Section: Methods Study Designmentioning
confidence: 99%
See 1 more Smart Citation